Representasi Gender dalam Film “Tenggelamnya Kapal Van Der Wijck” - Lailatul Mufarihah (Jurnal Ilmu Komunikasi, 2019)
Film is one of the mass media that influences changes in the construction of the audience's mindset. This article discusses gender that is brought back in the frame of the film "The sinking of the ship van der Wijck". The purpose of this study was to determine the gender construction displayed by the film media. This study uses a qualitative approach with media text analysis. The analysis used is the framing analysis model of William A. Gamson and Andre Modigliani, which emphasizes the media frame and package in packaging an idea. The result of this research is that gender in the film "Tenggelamnya Kapal van der Wijck" is represented by discrimination against women. The point is that women in this film in many parts are shown as oppressed and always blamed. In addition, women are given the impression of being worthless and are likened to buying and selling goods that can only be owned by those who have assets and position.